2017
DOI: 10.2399/yod.17.001
|View full text |Cite
|
Sign up to set email alerts
|

Students' Learning Outcomes in Massive Open Online Courses (MOOCs): Some Suggestions for Course Design

Abstract: M Massive Open Online Courses (MOOC) are built on the impression that "information is everywhere" by extending access to education. A MOOC is a course, but it is open, distributed, participatory, and part of lifelong network learning. The underlying idea of a MOOC is accessibility, since anyone can participate by working collaboratively either to acquire new knowledge or to expand existing knowledge. This implies that MOOCs create a pathway for lifelong learning processes. MOOCs are online classes in which any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 61 publications
2
35
0
1
Order By: Relevance
“…The effectiveness of an online course and ensuring student learning outcomes would be dependent on the quality of the course, user interface design, teacher characteristics, learning-focused activities and student characteristics. Providing proper feedback, encouraging learning networks, providing flexible structure, material and support are essential to retain students and ensure course completion [56].…”
Section: Methodsmentioning
confidence: 99%
“…The effectiveness of an online course and ensuring student learning outcomes would be dependent on the quality of the course, user interface design, teacher characteristics, learning-focused activities and student characteristics. Providing proper feedback, encouraging learning networks, providing flexible structure, material and support are essential to retain students and ensure course completion [56].…”
Section: Methodsmentioning
confidence: 99%
“…Understanding which factors account for students' effective learning in open online courses an important step toward is designing efficacious courses and improving open online learning. [2] In this section, the author attempts to explore essential elements in effective MOOC-based English learning environment based on Biggs's 3P Model.…”
Section: Essential Elements In Effective Mooc-based English Learning mentioning
confidence: 99%
“…Based on the literature review, two elements in the visual learner dimension were identified: (1) learn best from what they see, and (2) learners priorities pictorial materials. While seven elements in the active learner dimension were identified: (1) learn by trying things, (2) can be impulsive, (3) risk-takers, (4) do not prefer lectures, (5) interpersonal, (6) prefer group work and (7) participate in learning tasks immediately. Based on findings from RQ1, the researchers proposed an existing element learning styles (visual and active) in adaptive self-assessment activities for improving student performance using MOOCs learning for the second language course.…”
Section: A Research Question 1: What Are the Learning Styles Of Learmentioning
confidence: 99%
“…In MOOC assessment, the issue is, there was a reduction of interest and activity of students during the session of the course [5]. Three requirements to designing effective online course are (1) learners characteristics, (2) context and (3) activities [6]. These authors suggest a reconceptualization of (1) curriculum activities and (2) student achievement based in various indicators of performance.…”
Section: Introductionmentioning
confidence: 99%